2017
DOI: 10.4103/0973-1482.187279
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of cervical cancer and willingness to participate in screening program: Public health policy implications

Abstract: The country's national program advocates for opportunistic and targeted screening of women. An understanding of the factors that influences womens' willingness to participate in screening program is essential for the success of such programs. Hence, this study emphasizes the need for dissemination of knowledge about various aspects of cancer cervix which is critical for uptake of any screening program in a developing country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 1 publication
3
29
1
Order By: Relevance
“…In present study the compliance and willingness of undergoing Cervical examination and Pap test was 85.3% while in Patra S et al study, 24.1% women were willing to go for pap test examination. 11 In contrary to that 78.8% compliance was seen in Bhagwan N et al study. 12 And 94.6% women had undergone pap test examination in Sherpa A et al study.…”
Section: Discussionmentioning
confidence: 71%
“…In present study the compliance and willingness of undergoing Cervical examination and Pap test was 85.3% while in Patra S et al study, 24.1% women were willing to go for pap test examination. 11 In contrary to that 78.8% compliance was seen in Bhagwan N et al study. 12 And 94.6% women had undergone pap test examination in Sherpa A et al study.…”
Section: Discussionmentioning
confidence: 71%
“…Overall, 77 papers and one dissertation were eligible for analysis and were listed in the order of publication years. [171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788899091929394] The review process is explained in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The studies consist of different populations such as women and men from different community groups[17202425313235394143454751616669717379808586909293]And attended clinics[2729425259676872757682]Students (nursing/medical/paramedical/nonmedical)[3840464850565860646974818389]Health-care providers (doctors, nurses, and other health workers);[1828365354555657626365667778889194] migrated Indians;[1921262730333437498487] and cervical cancer patients. [23]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Further, several studies have found that educating women on their cervix and cervical cancer significantly increased cervical cancer screening rates more than two-fold. 18,19,[23][24][25][26][27][28][29] Simply put, giving women access to accurate information and a comprehensive education on their sexual anatomy can significantly improve their understanding of sexual and reproductive health. One strategy to empower women to care and advocate for their reproductive autonomy is the provision of self-exploration technology that facilitates women's visualization, understanding and appreciation of their own vagina and cervix.…”
Section: Introductionmentioning
confidence: 99%